The triple-helical DNA four-way junction - Makube, Neo (Department of Molecular and Cell Biology, 2018)
This Thesis will show that third strands can be incorporated into the four-way junctions combining the properties of the triple helices and those of branched structures within one system without compromising either of the two. It is now known that folding into secondary and tertiary structures by nucleic acids is crucial for their biological functions. However, what remain to be clarified are the mechanisms involved in the folding of nucleic acids into -noncanonical structures. It requires a thorough understanding of the chemical and physical properties of the structure in question. This in tum will improve the design of new secondary and tertiary structures that may add to the DNA nanotechnology. With this aim, thermodynamic and structural properties of two triple-helical DNA fourway junctions (JTIT3 and JT2T4) are reported and discussed. JTIT3 and JT2T4 differ only in the polarity of the third strands (and/or position of the loops). Both junctions contain the same Watson-Crick double-helical four-way junction, named Js, as a core structure. Js was constructed from four 20-mer oligomers, two of which consists of purines and the other two strands pyrimidines. Extending each of the pyrimidine strands of Js at the 3' end by four cytosines followed by twenty pyrimidine bases results in JTIT3. Similarly, JT2T4 is formed by extending the same pyrimidine strands at the 5' end. The junctions are named according to the position of the C4-loops. JTIT3 and JT2T4 are further simplified into JT1, JT2, JT3 and JT4. Lowering the pH from 12 to 2 allows the oligomers to fold sequentially from random coil into the double-helical four-way junction, Js, and finally into the triple-helical four-way junction. The analysis of the structures discussed is based on the biochemical methods such as native polyacrylamide gel electrophoresis and chemical footprinting using osmium tertroxide as a probe. The analysis is also based on the physical methods, UV spectroscopy and DSC. The native polyacrylamide gel electrophoresis has been used to verify the formation of the complete four-way junctions. Chemical footprinting has been used to detect the formation of the junctions as well as to indicate the conformations these junctions assume under different pH and/or salt conditions. The phase diagrams enthalpies and entropies of the structures are determined mainly by DSC. The results indicate that all the junctions are highly sensitive to salt concentrations and/or pH. The Tm vs. [Na+] results show that above 0.4M Na+, the structures adopt a conformation that suggests that the junctions are folded into stacked helix structures. The differences in thermal stabilities of the junctions JT1, JT2, JT3 and JT are due to the sequence composition of the arms and not the loops. JT1, JT2, JT3 and JT4 are thermally more stable than the underlying double-helical junction, Js. Similarly; the complete triple-helical four-way junctions JTIT3 and JT2T4 are thermally more stable than their substructures JT1, JT2, JT3 and JT4, The compiled transition enthalpies obtained for the individual arms of Js, JT1, JT2, JT3 and JT4 are less than the transition enthalpies associated with the melting of the complete junctions. The higher calorimetric enthalpies of the structures are due in part to the contribution from the single strands resulting from the partly unfolded arms. The overall results show that third strands have a stabilizing effect on the structure of the four-way junction.